Managing Curriculum Development in Islamic Boarding Schools: Integrating Faith and Pedagogical Values. - Zuhair Mubarrak Hazaa; Dinda Puteri Rezeki; Khairul Ameer; Candra Wijaya; Rahmat Hidayat (Journal La Edusci, 2025)
This study examines curriculum needs in Islamic boarding schools through a qualitative needs analysis approach grounded in in depth interviews with key educational stakeholders. Participants included teachers students curriculum division staff and institutional leaders who are directly involved in curriculum enactment and decision making within the pesantren system. The study aims to explore how curriculum needs are experienced and articulated across different roles and to identify shared priorities that can inform value oriented curriculum development. Data were analyzed thematically to capture recurring patterns of needs embedded in everyday educational practices. The findings reveal that curriculum needs in Islamic boarding schools are systemic and relational rather than technical in nature. Participants consistently emphasized the importance of meaningful integration of Islamic values across subjects pedagogical flexibility learning relevance and coherent evaluation practices. These needs reflect a shared aspiration to maintain Islamic identity while responding to contemporary educational demands. The study concludes that a needs driven and participatory approach provides a robust foundation for curriculum reform in Islamic boarding schools by aligning curriculum development with lived experiences institutional values and future oriented educational goals.